Discovery of a novel binding pocket for CYP 2C9 inhibitors: crystallography, pharmacophore modelling and inhibitor SAR. Issue 5 (11th February 2016) - Skerratt, Sarah E.; de Groot, Marcel J.; Phillips, Chris
Abstract : CYP 2C9 co-crystal structures of compound1 (green) in binding mode 1 (CYP 2C9 in green) and compound2 (yellow) in binding mode 2 (CYP 2C9 in yellow). Abstract : Herein, we describe the discovery of a novel binding pocket for CYP 2C9 inhibitors. Trifluoromethanesulfonamide compounds1 and2, identified within a Pfizer progesterone receptor antagonist program, were found to strongly inhibit the drug metabolizing cytochrome P450 enzyme CYP 2C9. Homology modelling and subsequent X-ray co-crystal data have elucidated the binding orientation of compounds1 and2 in CYP 2C9. Compound2 adopts a previously unreported binding mode. Less acidic sulfonamide analogues within these series have reduced CYP 2C9 activity, and we postulate this is due to a reduced hydrogen bonding potential with key interacting residues within CYP 2C9. This work shows that CYP 2C9 has a more flexible active site than previously reported; therefore multiple binding modes and alternative pharmacophore models must be considered when predicting CYP 2C9 affinity.